2017
DOI: 10.1101/173252
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

BLM helicase suppresses recombination at G-quadruplex motifs in transcribed genes

Abstract: Bloom syndrome is a cancer predisposition disorder caused by mutations in the BLM helicase gene. Cells from persons with Bloom syndrome exhibit striking genomic instability characterized by excessive sister chromatid exchange events (SCEs). We applied single-cell DNA template strand-sequencing (Strand-seq) to map the genomic locations of SCEs at a resolution that is orders of magnitude better than was previously possible. Our results show that, in the absence of BLM, sister chromatid exchanges in human and mur… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 64 publications
1
21
0
Order By: Relevance
“…Given the high prevalence of G4 at promoters and transcribed loci (Hänsel-Hertsch et al, 2016) this raises the interesting possibility that BLM may be a bona fide component of TC-DSBR which activity may be particularly relevant at transcribed, G4-forming, damaged loci. In agreement, Strand-seq experiments revealed that sister chromatid exchange (SCEs) breakpoints observed in BLM-deficient cells are biased toward G4 motifs, especially those present in transcribed genes (van Wietmarschen et al, 2018).…”
Section: Introductionsupporting
confidence: 54%
“…Given the high prevalence of G4 at promoters and transcribed loci (Hänsel-Hertsch et al, 2016) this raises the interesting possibility that BLM may be a bona fide component of TC-DSBR which activity may be particularly relevant at transcribed, G4-forming, damaged loci. In agreement, Strand-seq experiments revealed that sister chromatid exchange (SCEs) breakpoints observed in BLM-deficient cells are biased toward G4 motifs, especially those present in transcribed genes (van Wietmarschen et al, 2018).…”
Section: Introductionsupporting
confidence: 54%
“…Aberrant function of the G4-resolving helicases WRN and BLM result in altered transcription of genes containing G4 motifs in their promoter region, corroborating a link between G4s and transcription [107,108]. Moreover, BLM-mutated cells derived from Bloom syndrome patients show high rates of sister chromatid exchange at sites of G4 motifs in transcribed genes [109]. Notably, these helicases also process duplex DNA, so not all the observed changes may be linked to G4 structures.…”
Section: Biological Role Of G4smentioning
confidence: 91%
“…In proliferating cells, G4 act as replication fork barriers, provoking fork collapses, the activation of the DNA damage response and the induction of replication-dependent DSBs (13). However, increasing evidence indicates also a significant impact of G4 structures on genomic stability through transcriptiondependent processes (5,(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%